Comparative effectiveness, growth and dispersal of stocked Arctic char (Salvelinus alpinus) from different origins in lake Annecy - Janjua, Muhammad; Zanella, Damien; Gerdeaux, Daniel (Knowledge and Management of Aquatic Ecosystems, 2010)
International audience